THE EFFECTIVENESS OF GAMES TO TEACH ENGLISH IN INDONESIAN CONTEXT - Khudriyah . (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2021)
ABSTRACT Teaching English as foreign language in Indonesia consists of four skills (listening, speaking, reading, and writing), and other aspects such as, grammar, vocabulary, pronunciation, and so forth. It is hard work, so it needs the methods or strategies that are interesting and enjoyful. One of them is games. Many experts and researchers that games is an attractive, and effective way to teach foreign language. This article discusses the findings of research about teaching English using games to improve the English skills, and some aspects. This research is descriptive qualitative, which based on the finding of eight researchs result. The research finding can be concuded that games is effective to teach vocabulary, structure, pronunciation, and speaking. Because it can improve the students score. Besides, the students are more actively involved in the teaching and learning process. Keywords: effectivenes, games, teach, foreign language